(untitled) (Medico Legal Update, 2019)
Background: The professionals working in a hospital, especially the clinical staff will have to deal with many medical cases which have legal implications. Health care providers are at high risk for litigations. Being aware about medico legal aspects and importance of documentation and performing their duties ethically can safeguard themselves against risks of litigation. Objective: To assess the awareness among health professionals about legal practices and medical documentation in patient care. Method: A crosssectional study was carried out with the help of a validated and pre-tested questionnaire involving 219 health professionals belonging to different disciplines of allied health sciences and nursing at a tertiary care hospital in south India. Result: The study showed that the professionals who were involved indirectly, such as pharmacists and health information management professionals scored less than 50% of the total knowledge score while those involved in direct clinical care such as physiotherapists and nurses scored more than 50% of the total knowledge score, and hence better. Similarly professional with three or more years of experience scored above 50% and hence better than professionals with lesser experience. The responses indicated that, the respondents were only able to attain a score around 50% of the maximum attainable. Conclusion: The findings indicate there is a need of bringing on the awareness about the various aspects of medico-legal cases in patient care. This is not only for professional safety but also for the safety of patients at large. Hospital and their administrators should regularly conduct sensitisation programs on medico legal aspects in patient care and importance of documentation